2020
DOI: 10.18311/jnr/2020/24172
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bee Honey on Wound Healing: Split Skin Graft with Hyper-granulation Tissue

Abstract: The present prospective study was aimed to evaluate the effectiveness of topical application of bee honey on wound healing with hyper granulation tissue of infected split skin graft. Methods: A 27 years old female was admitted to Khartoum North Teaching Hospital plastic surgery unit with painful swelling of the right buttock with localized heat, which was proved as a pyogenic abscess. Swabs were taken from the wound for isolation, identification and viable bacterial count. The abscess was drained under general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Grecka et al (2018) found that honey produced by Polish apiaries can be used as an alternative agent for treating staphylococcal infections. Wadi & Geregandi (2020) demonstrated that the growth of this Gram+ was strongly inhibited after a topical application of honey on an infected wound by this bacterial pathogen. All of the tested honey (San Francisco, Elshifa, Zriba and Sidi Achour) had an inhibitive effect against this pathogenic germ to high concentrations (75% and 100%), and Zriba honey as well at 50%.…”
Section: Antibacterial Activitymentioning
confidence: 95%
“…Grecka et al (2018) found that honey produced by Polish apiaries can be used as an alternative agent for treating staphylococcal infections. Wadi & Geregandi (2020) demonstrated that the growth of this Gram+ was strongly inhibited after a topical application of honey on an infected wound by this bacterial pathogen. All of the tested honey (San Francisco, Elshifa, Zriba and Sidi Achour) had an inhibitive effect against this pathogenic germ to high concentrations (75% and 100%), and Zriba honey as well at 50%.…”
Section: Antibacterial Activitymentioning
confidence: 95%
“…Honey is one of the natural ingredients that has been used to treat wounds for thousands of years [4]. In the past few years, some research has also proven the effectiveness of honey for wound healing [5][6][7]. Honey is produced by the bees by modifying the nectar gathered from the plants.…”
Section: Introductionmentioning
confidence: 99%